The Effect of Slow Deep Breathing and Warm Water Foot Bathing on Blood Pressure Reduction in Hypertensive Patients - Suryandari, Dewi; Ningrum, Arlindha Rahayu (GLOBAL HEALTH SCIENCE GROUP, 2024)
Hypertension is one of the silent killers as it often does not produce noticeable symptoms, and patients become aware of it only when the perceived illness has become severe. Hypertension could lead to complications if not promptly managed, and its management can be either pharmacological or non-pharmacological. Non-pharmacological approaches to reducing blood pressure are increasingly being studied, including the combination therapy of slow-deep breathing and warm water foot bathing. Slow-deep breathing involves slow and deep respiratory relaxation, while warm water foot bathing is a relaxation technique that utilizes warm water as a medium. The study aimed to determine the effect of slow-deep breathing and warm water foot bathing on blood pressure reduction in hypertensive patients. The research employed a quasi-experimental method with a pre-test and post-test approach without a control group. The total sampling was 24 respondents. The data were analyzed using the Wilcoxon statistical test. The study revealed pre-intervention that the average systolic blood pressure was 160.63 mmHg, and the diastolic blood pressure was 95.42 mmHg. Post-intervention presented the average systolic blood pressure reduced to 140.42 mmHg, and the diastolic blood pressure decreased to 86.04 mmHg. The Wilcoxon test results obtained that the systolic blood pressure had a p-value of 0.000 (p-value < 0.05), and the diastolic blood pressure had a p-value of 0.000 (p-value < 0.05). Based on these results, there was an effect of slow-deep breathing and warm water foot bathing on blood pressure reduction in hypertensive patients.